The osier cage : rhetorical devices in Romeo & Juliet - Evans, Robert O. (Robert Owen), 1919- (University of Kentucky Press, 1966)
By studying the diction of Romeo and Juliet, Robert O. Evans examines this, the most rhetorical of Shakespeare's plays, in terms of an Aristotelian critical category, which has been neglected in modern times. Inherent in his methodology is the assumption that Romeo and Juliet is best regarded as drama, not as pure poetry, though essentially it is the rhetorical brilliance of the poetry that is considered. Evans begins with an analysis of the important speeches of Romeo and Juliet and defines the controlling devices Shakespeare wove into them, especially oxymoron. He then follows with a discu.